Renal PEComa in a young male: A case report and insights from the literature - Rashad Sholan; Rufat Aliyev; Malahat Sultan; Anar Almazkhanli; Savalan Karim; Jalal Gasimov (Urology Case Reports)
Perivascular epithelioid cell tumors (PEComas) are rare mesenchymal neoplasms, commonly found in the uterus and retroperitoneum. Renal PEComas are exceedingly rare, often posing diagnostic challenges due to their resemblance to renal cell carcinoma (RCC) on imaging. We present the case of an 18-year-old male who presented with non-specific symptoms of fever, chills, and shivering. Imaging revealed a renal mass, initially suspected to be RCC. However, following a right radical nephrectomy, histopathological examination confirmed the diagnosis of malignant PEComa. This case highlights the rarity of renal PEComa and underscores the importance of early diagnosis and appropriate surgical management to prevent complications.